(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In this paper, we introduce a ghost-free High Dynamic Range imaging algorithm for obtaining ghost-free high dynamic range (HDR) images. The multiple image fusion based HDR method work only on condition that there is no movement of camera and object when capturing multiple, differently exposed low dynamic range (LDR) images. The proposed algorithm makes three LDR images from a single input image to remove such an unrealistic condition. For this purpose a histogram separation method is proposed in the algorithm for generating three LDR images by stretching each separated histogram. An edge-preserving denoising technique is also proposed in the algorithm to suppress the noise that is amplified in the stretching process. In the proposed algorithm final HDR image free from ghost artifacts in dynamic environment because it self-generates three LDR images from a single input image. Therefore, the proposed algorithm can be use in mobile phone camera and a consumer compact camera to provide the ghost artifacts free HDR images in the form of either inbuilt or post-processing software application.